Developing the Service Sector as Engine of Growth for Asia: An Overview - Marcus Noland; Donghyun Park; Gemma B. Estrada (Asian Development Bank (ADB), 2012)
The maturing of the manufacturing sector in many Asian countries, combined with the relative backwardness of its service sector, has made service sector development a top priority for developing Asia. Our central objective is to broadly survey and analyze the current landscape of the region's service sector so as to assess its potential to serve as an engine for inclusive economic growth. Our analysis indicates that services are already an important source of output, growth, and jobs in the region. However, its productivity greatly lags that of the advanced economies, which implies ample room for further growth. The impact of service sector on poverty reduction is less clear but we do find some limited evidence of a poverty reduction effect. One key challenge for all Asian countries is to improve the quality of service sector data. Overall, while service sector development is a long and challenging process, creating more competitive services markets by removing a wide range of internal and external policy distortions is vital for improving service sector productivity. As important as such policy reforms are, complementary investments in physical infrastructure and human capital will also be necessary to achieve a strong service sector.
hdl:11540/1270
Keywords: 330; Dienstleistungssektor; Strukturwandel; Produktivität; Wirtschaftswachstum; Asien